2021
DOI: 10.3390/ijms22073352
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Role of High-Density Lipoprotein in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is a highly prevalent malignancy with multifactorial etiology, which includes metabolic alterations as contributors to disease development. Studies have shown that lipid status disorders are involved in colorectal carcinogenesis. In line with this, previous studies have also suggested that the serum high-density lipoprotein cholesterol (HDL-C) level decreases in patients with CRC, but more recently, the focus of investigations has shifted toward the exploration of qualitative properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 188 publications
0
23
0
Order By: Relevance
“…Changes in HDL levels, HDL particle distribution, and HDL receptors and modulators have been consistently found in CRC patients [ 61 ]. HDL is, so far, the most complex lipoprotein particle, and it is now clear that its role both in health and in disease also includes an antioxidant, anti-inflammatory, immunomodulatory, anti-apoptotic, and anti-thrombotic functions [ 62 ]. Several studies have shown that HDL particles can stimulate the growth of breast cancer cells in vitro, as well as increase the aggressiveness of malignant tumours in mice [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in HDL levels, HDL particle distribution, and HDL receptors and modulators have been consistently found in CRC patients [ 61 ]. HDL is, so far, the most complex lipoprotein particle, and it is now clear that its role both in health and in disease also includes an antioxidant, anti-inflammatory, immunomodulatory, anti-apoptotic, and anti-thrombotic functions [ 62 ]. Several studies have shown that HDL particles can stimulate the growth of breast cancer cells in vitro, as well as increase the aggressiveness of malignant tumours in mice [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that insulin stimulates proliferation of Caco-2 and HT-29 cell lines [30] but also enhances cholesterol uptake and lipid accumulation in Caco-2 cells through elevation of cholesterol transporter scavenger receptor, class B, type I (SR-BI) mRNA, and protein levels [31]. This latter effect of insulin might be of special interest, noting the increasing demand of malignant cells for cholesterol and evidence of disturbed lipid homeostasis in CRC [32,33]. Molecular mechanisms that directly link insulin action and the onset and progression of CRC are suggested by a number of studies.…”
Section: Insulin Resistancementioning
confidence: 99%
“…For instance, the transcription factor RORγ was found to be up-regulated and activate the cholesterol biosynthesis in triple-negative breast cancer cells [ 9 ]. Additionally, the uptake and the accumulation of cholesterol increase in CRC cells which promote their proliferation, and cancer occurrence and development seem to be associated with the consumption of circulating cholesterol by the tumor [ 10 – 12 ]. Therefore, hypercholesteremia potentially maintains sufficient cholesterol uptaken by tumors that accelerate the growth.…”
Section: Introductionmentioning
confidence: 99%